2020
DOI: 10.1080/16742834.2020.1746175
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the simulation of the summer East Asian westerly jet from CMIP5 to CMIP6

Abstract: The East Asian westerly jet (EAJ) plays a crucial role in affecting the East Asian summer rainfall (EASR). Therefore, evaluations of EAJ simulations are vital for improving the understanding and projections of climate change in East Asia. This study evaluates the simulations of the climatology and interannual variability in the present-day summer EAJ in the CMIP6 models and compares the results with those in the CMIP5 models by analyzing the historical climate simulations of 29 CMIP5 models and 21 CMIP6 models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Several studies have assessed CMIP6 by comparing the historical simulation data of CMIP5 and CMIP6 with the observed data (Gusain et al, 2020;Yuanhai et al, 2020;Zamani et al, 2020;Zhu and Yang 2020). When CMIP5 and CMIP6 are compared, the multimodel mean result (Xin et al, 2020;Yuanhai et al, 2020) rather than a specific GCM (Wyser et al, 2020) is used in most cases. Gusain et al (2020) compared CMIP6 and CMIP5 when simulating Indian summer monsoon precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed CMIP6 by comparing the historical simulation data of CMIP5 and CMIP6 with the observed data (Gusain et al, 2020;Yuanhai et al, 2020;Zamani et al, 2020;Zhu and Yang 2020). When CMIP5 and CMIP6 are compared, the multimodel mean result (Xin et al, 2020;Yuanhai et al, 2020) rather than a specific GCM (Wyser et al, 2020) is used in most cases. Gusain et al (2020) compared CMIP6 and CMIP5 when simulating Indian summer monsoon precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with CMIP5, CMIP6 models have a certain degree of improvement and development in terms of resolution, physical parameterization, experimental design, and simulation computing capability. The simulation of the climate models from CMIP6 was closer to the observed value, while the uncertainty of simulation was smaller and the accuracy of the simulation was higher [26][27][28]. Taking the study of extreme climate indices as an example, the climate models from CMIP6 had stronger effects on the extreme temperature indices and extreme precipitation indices than the climate models from CMIP5, which can well reproduce the changing trend of the extreme climate indices [71,72].…”
Section: Discussionmentioning
confidence: 74%
“…Since the implementation of CMIP was more than 20 years, the number of participating models for CMIP6 was the largest, the scientific experiment design was the most complete, and the largest amount of model data was provided [25]. Compared with previous climate models such as CMIP5, the simulations of CMIP6 models for climate systems were closer to the observations and had less uncertainty, so the simulating ability of climate change has significantly improved [26,27]. For example, in terms of simulation for extreme climate at global scale, CMIP6 models had a general improvement in simulating the changing trend of extreme climate compared to CMIP5 models [28].…”
Section: Introductionmentioning
confidence: 99%
“…7). The BIAS is -1.0 gpm (MPI-ESM1-2-HR) to -21.3 gpm (MIROC6) at a pressure level of 850 hPa and -1.1 gpm westerlies, which was reported by Fu et al (2020). Moreover, it was reported that such underestimation exists in both CMIP5 and CMIP6 models (Fu et al 2020).…”
Section: Geopotential Heightmentioning
confidence: 78%